Human Milk From Atopic Mothers Has Lower Levels of Short Chain Fatty Acids - Stinson, Lisa F.; Gay, Melvin C. L.; Koleva, Petya T.; Eggesbø, Merete; Johnson, Christine C.; Wegienka, Ganesa; du Toit, Elloise; Shimojo, Naoki; Munblit, Daniel; Campbell, Dianne E.; Prescott, Susan L.; Geddes, Donna T.; et al. (Frontiers in Immunology, 2020)
Short chain fatty acids (SFCAs) are microbial metabolites produced in the gut upon fermentation of dietary fibre. These metabolites interact with the host immune system and can elicit epigenetic effects. There is evidence to suggest that SCFAs may play a role in the developmental programming of immune disorders and obesity, though evidence in humans remains sparse. Here we have quantified human milk (HM) SCFA levels in an international cohort of atopic and non-atopic mothers (n = 109). Our results demonstrate that human milk contains detectable levels of the SCFAs acetate, butyrate, and formate. Samples from atopic mothers had significantly lower concentrations of acetate and butyrate than those of non-atopic mothers. HM SCFA levels in atopic and non-atopic women also varied based on maternal country of residence (Australia, Japan, Norway, South Africa, USA). Reduced exposure to HM SCFA in early life may program atopy or overweight risk in breastfed infants.